Development of an automated three-phase distribution box system - Nor, N.M. (Institute of Advanced Engineering and Science, 2017)
Most electrical appliances require continuous power supply. For domestic use, crucial appliances such as refrigerator, aquarium and alarm system highly depend upon the continuity of power supply. However, if they are left without electricity due to power outage or blackouts caused by internal or external disturbance, the discontinuity of power supply could be a critical issue to some involving party. Blackouts may be due to short circuit, fault or the overloading of electricity mains. During power outage, Residual Current Device (RCD) detects fault currents from live to the neutral wire within circuit and will trip to prevent shock. This circumstance can increase safety when a house is left unoccupied. Be that as it may, the power will remain switched off until manually reset by man. Thus, this paper presented a new concept of Three-Phase distribution box system in order to overcome tripping problem. This system will be able to identify and isolate the fault using measurement of current flow into each Miniature Circuit Breaker (MCB) of appliances and current flowing out from each of the load. The measured current value will be compared and the maximum allowable difference is 30mA. If the current difference exceeds the maximum limit then the fault MCB will be detected. Hence RCD will be automatically close the circuit after determining the fault location via the motor operation to make sure of power stability and evade any property loss. © 2017 Institute of Advanced Engineering and Science. All rights reserved.